The effect of lactation stage on the hematological and serum-related biochemical parameters of the Travnik pramenka ewes - Antunović, Zvonko (Array, 2021)
The aim of the present research was to determine the hematological and biochemical parameters of the Travnik pramenka ewes during lactation. Thirty‐six ewes in average age of 3-5 years were included in the research. They were monitored in three stages of lactation: early, medium, and late stage. The WBC and RBC, HGB concentration, HCT and MCH values increased significantly as lactation progressed, while significant decrease of MCV and MCHC was determined in blood. HCT was slightly higher in the early compared to late stage, and the MCH in the medium compared to the late stage of lactation. A significant increase in the concentrations of Ca, P, Mg, Na and Cl, as well as a decrease of the Fe concentration was determined. As lactation progressed, the concentrations of urea, total proteins, albumin, globulin and BHB increased, as well as ALT activity. Contrary, concentrations of glucose and NEFA decreased, as well as GGT activity. Obtained results may help in monitoring the health and nutritional status of Travnik ewes. The effect of lactation stage needs to be included in the model when preparing the reference values for the blood parameters of Travnik pramenka ewes, particularly for RBC profiles, energy, and protein metabolites as well as liver enzymes.